2014
DOI: 10.1007/s12264-014-1445-5
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune responses regulate morphogenesis and degeneration: roles of Toll-like receptors and Sarm1 in neurons

Abstract: The central nervous system is recognized as an immunoprivileged site because peripheral immune cells do not typically enter it. Microglial cells are thought to be the main immune cells in brain. However, recent reports have indicated that neurons express the key players of innate immunity, including Toll-like receptors (TLRs) and their adaptor proteins (Sarm1, Myd88, and Trif), and may produce cytokines in response to pathogen infection. In the absence of an immune challenge, neuronal TLRs can detect intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 60 publications
0
36
0
1
Order By: Relevance
“…) particularly as recent studies suggest that neurons may possess the necessary components to sense bacterial infection, thus acting as a trigger for innate immunity signalling (Liu et al . ). Indeed, LPS inhibition of AMPK expression in vivo is not limited to adult tissue as a very recent paper described the same phenomenon in weaned piglets (Kang et al .…”
Section: Discussionmentioning
confidence: 97%
“…) particularly as recent studies suggest that neurons may possess the necessary components to sense bacterial infection, thus acting as a trigger for innate immunity signalling (Liu et al . ). Indeed, LPS inhibition of AMPK expression in vivo is not limited to adult tissue as a very recent paper described the same phenomenon in weaned piglets (Kang et al .…”
Section: Discussionmentioning
confidence: 97%
“…Regardless, neuronal expressions of TLRs have been demonstrated by multiple studies (Liu et al, 2014). Expressions of TLR1, TLR2, TLR3, and TLR4 have been detected in human NT2-N neuronal cell line (Lafon et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recent study showed that expression and activation of neuronal TLR2 and 4 contributed to neurodegeneration by ischemic stroke (Tang et al, 2007). Studies have also suggested the roles of TLRs, such as TLR3, TLR7, and TLR8, in neural morphogenesis (Liu et al, 2014). Activation of TLR3 induces growth-cone collapse and inhibits neurite outgrowth in cultured dorsal root ganglion, cortical, and hippocampal neurons (Cameron et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Blood-borne and neural routes of communication between the peripheral and central nervous systems have been well-defined (Dinarello et al, 1988; Ericsson et al, 1994; Maier, 2003) and systemic immune challenge dramatically alters neural activity (Barrientos et al, 2015; Chapman et al, 2010; Maier and Watkins, 1998) and ablates the production of new highly excitable hippocampal granule neurons (Chen et al, 2011; Ekdahl et al, 2003; Ekdahl et al, 2009; Monje et al, 2002; Monje et al, 2003; Ormerod et al, 2013). Systemic inflammation can stimulate the de novo synthesis of brain parenchymal cytokines primarily by microglia (Layé et al, 1996; Nguyen et al, 1998; Van Dam et al, 1995) but also by other CNS cells (Liu et al, 2014; Vincent et al, 1998). In turn, neuroinflammation can impact the production of systemic cytokines (Campbell et al, 2007).…”
Section: Discussionmentioning
confidence: 99%